Nanoliter Analyte Sensing on Hybrid Plasmonic-biosilica Nanostructured Materials. (2017) - Kong, Xianming; Xi, Yuting; LeDuff, Paul; Rorrer, Gregory L.; Wang, Alan X.
Abstract: We developed a new strategy of optofluidic analysis from inkjet-printed droplets on photonic crystal biosilica-diatom at nanoliter scales. The hydrophilic diatom surface could concentrate target molecules in the liquid droplets as the solvent evaporates, which enables 2, 4, 6-trinitrotoluene (TNT) detection down to 2.7×10 -15 grams by surface-enhanced Raman scattering (SERS).